Pelaksanaan Kebijakan tentang Penerbitan Surat Persetujuan Berlayar (SPB) di Kantor Kesyahbandaran oleh PT. Multi Jaya Samudera Belawan - Sandryco Dame P Panggabean; Dirhamsyah Dirhamsyah; Taruna Ginting (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
This research examines the implementation of Sailing Approval Letter (SPB) issuance policy at the Harbor Master's Office by PT. Multi Jaya Samudera Belawan. SPB is an official document that must be possessed by every vessel before sailing as a form of authorization and supervision to ensure shipping operations comply with safety and security standards established by port authorities. The research methodology employs qualitative and descriptive approaches through interviews, direct observation, and document analysis at the Harbor Master's Office. The SPB issuance process includes several stages: application receipt with attachments of administrative, health, and safety documents; administrative verification to ensure document completeness and validity; physical vessel inspection of safety equipment completeness, technical conditions, security systems, and environmental compliance; SPB issuance as valid proof of sailing authorization; monitoring during voyage; documentation report issuance; and periodic procedure evaluation. Research findings indicate that PT. Multi Jaya Samudera implements SPB issuance in accordance with applicable regulations. However, obstacles encountered include delays in document submission due to vessel unpreparedness and inadequate internal administration, time-consuming physical vessel inspections, lack of coordination among related agencies, complex procedures, limited human resources at the Harbor Master's Office, technology and infrastructure constraints, rapid regulatory changes, and adverse weather conditions. The research recommends enhanced officer training, thorough document verification before submission, and updates to procedures and supporting facilities to improve the efficiency and effectiveness of the SPB issuance process.